Extraction, purification, and characterization of green mussel adhesive proteins (PVFP-5) - Lim, Ee Tat (2011)
Mussel adhesive proteins are found in plaques of mussel species in our marine and freshwater environments. Through evolution, mussels have developed adhesive mechanisms to help them survive the wave impacts in intertidal zone areas as well as deep in the sea where strong currents are present. Other than being a favorite model for studying bio-fouling, mussel adhesive proteins have long been studied due to the fact that the strong adhesive properties might provide novel insights into bio-adhesive mechanisms. The purpose of this project is to create a protocol effective for extraction and purification of PVFP-5, an adhesive protein predicted to occur in Perna viridis, a common bio-fouling species found in the Singapore. The findings in this report would set as a basis for future purification of mussel adhesive proteins at NTU. Results showed Arnow positive stains of centrifuged pellets from crude protein extracts based on published methods for a different mussel species. The data indicates that the extract contains a side chain modification of tyrosine known as DOPA, which is known to be present in large amounts in mussel adhesive proteins. Colorimetric analysis of the pellet solution using UV-Vis spectrophotometer also indicated a slight absorption near the 500nm range, supporting the theory that DOPA containing proteins were present. Reverse phase HPLC results of the crude extract showed a broad distribution of material, in particular at the 280nm wavelength, which is specific for aromatic groups. HPLC and MALDI-TOF results indicate that a low molecular weight protein elutes at around 33 minute intervals under a flowrate of 0.7ml/min on the HPLC. The results showed that the published protocol for crude extraction of Mytilus edulis is not directly compatible for the purification of PVFP-5. While this finding is a negative result, the experiments provides backgrounds for future optimization of the protocol and suggests that PVFP-5 may have significant differences in protein chain chemistry and side chain modifications. Confirmation of this hypothesis would then represent a significant finding.